Study on the Distribution of Cereal Cyst Nematodes Heterodera spp. in Wheat and Barley Fields in Northern and Eastern Regions of Syria and the Definition of their Species (Damascus University Journal of agriculture sciences, 2024)
Study of distribution of cyst nematodes Heterodera spp. was conducted in 167 wheat and barley fields, in northern and eastern regions of Syria, after harvesting plants, 2009. Results showed that 62.28% of the surveyed fields were infested. Infestation ratios in Aleppo, Al-Hassakah, Idleb, Der Ezzor and Al-Raqqa governorates were 82.86, 72, 66.67, 50 and 20.29% of the total surveyed fields in each governorate, respectively. Based on morphological characteristics of the cyst vulval cone, three species of cereal cyst nematodes were identified: H. latipons Franklin where was found alone up to 67.31% of infested fields, and mixed with other species in 8.65%. H. avenae Wollenweber was found alone up to 20.19%, and mixed with other species in 10.58%. H. filipjevi (Madzhidov,1981) Stone which has limited distribution, it was found mixed with one or two species of cyst nematodes up to 8,65%.
Keywords: Survey; Syria; Wheat; Barley; Cereal Cyst Nematodes